Javanese Power: A Comparative Study of the Power Systems of the Majapahit and Demak Kingdoms - Yusep Munawar Sofyan (Trigin Publisher, 2021)
Majapahit and Demak were the two most influential Javanese kingdoms of their time. The two kingdoms are located in the same area, namely Java, but have many differences, including the problem of the concept of the legitimacy of power and the authority of the power possessed by the kings. As a Javanese kingdom that still holds the ancestral traditions of the two kingdoms, it is strengthened by religious teachings that are quite influential. Majapahit which adheres to Hindu-Buddhist religion and Demak adheres to Islamic teachings. The legitimacy that was later obtained by the Javanese rulers was the legitimacy of descent where the next royal ruler was the crown prince or a close relative of the kingdom, although the succession of leadership in order to gain legitimacy of power was not only obtained in a smooth way, namely there were several power struggles that ended in civil war, one example is the struggle for power for the sake of legitimacy, there was a war called Paregreg during the Majapahit era. Demak, which is different from Majapahit, still relies on genealogy as a reinforcement of the legitimacy of its power in the eyes of the people. Raden Fatah is the son of Brawijaya V, the last ruler of Majapahit. This certainly indicates that the legitimacy of descent became very dominant in the state administration of the ancient Javanese kingdoms. After a leader gains legitimacy, it will turn into a power authority that will be owned. Given the concept of centralized Majapahit power, so that the authority of power then lies in the hands of the king directly,